2018
DOI: 10.1111/psyg.12325
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness in Chinese older adults in primary care: prevalence and correlates

Abstract: Loneliness is common in Chinese primary care OA. The high prevalence and many negative health consequences of loneliness for OA highlight the importance of routine screening, assessment, and interventions to reduce loneliness in the primary health-care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 54 publications
5
61
2
Order By: Relevance
“…The aging people often experience age related problems and consequences, like functional limitations, psychological disorder, changes in social status, loss of confidence, loss of physical heath, these processes of late life may bring loneliness (Prince, Harwood, Blizard, Thomas, & Mann, 1997). However, living alone (Beutel et al, 2017;Grenade & Boldy, 2008;Havens, Hall, Sylvestre, & Jivan, 2004;Hellström, Persson, & Hallberg, 2004;Savikko et al, 2005;Steed, Boldy, Grenade, & Iredell, 2007;Wenger, Davies, Shahtahmasebi, & Scott, 1996;Zhong, Liu, Chen, Chiu, & Conwell, 2018) advancing of age (Hellström et al, 2004;Savikko et al, 2005;Zhong et al, 2018) gender (Hellström et al, 2004;Jylhä, 2004;Stessman et al, 1996) level of education (Savikko et al, 2005;Zhong et al, 2018) , place of residence (Savikko et al, 2005;Zhong et al, 2018) visual and hearing impairments (Mullins, Elston, & Gutkowski, 1996;Savikko et al, 2005;Zhong et al, 2018) widowhood (Grenade & Boldy, 2008;Hellström et al, 2004;Savikko et al, 2005;Stessman et al, 1996) co-morbid illness (Hellström et al, 2004) and depression (Beutel et al, 2017;Chrostek, Grygiel, Anczewska, Wciórka, & Świtaj, 2016;Pinquart & Sorensen, 2001;Sündermann, Onwumere, Kane, Morgan, & Kuipers, 2014;Switaj, Grygiel, Anczewska, & Wciórka, 2014) have been found highly significantly associated with loneliness in older adults in previous studies. The portion of older citizens has been increasing worldwide and Bangladesh is not exception of this.…”
Section: Introductionmentioning
confidence: 99%
“…The aging people often experience age related problems and consequences, like functional limitations, psychological disorder, changes in social status, loss of confidence, loss of physical heath, these processes of late life may bring loneliness (Prince, Harwood, Blizard, Thomas, & Mann, 1997). However, living alone (Beutel et al, 2017;Grenade & Boldy, 2008;Havens, Hall, Sylvestre, & Jivan, 2004;Hellström, Persson, & Hallberg, 2004;Savikko et al, 2005;Steed, Boldy, Grenade, & Iredell, 2007;Wenger, Davies, Shahtahmasebi, & Scott, 1996;Zhong, Liu, Chen, Chiu, & Conwell, 2018) advancing of age (Hellström et al, 2004;Savikko et al, 2005;Zhong et al, 2018) gender (Hellström et al, 2004;Jylhä, 2004;Stessman et al, 1996) level of education (Savikko et al, 2005;Zhong et al, 2018) , place of residence (Savikko et al, 2005;Zhong et al, 2018) visual and hearing impairments (Mullins, Elston, & Gutkowski, 1996;Savikko et al, 2005;Zhong et al, 2018) widowhood (Grenade & Boldy, 2008;Hellström et al, 2004;Savikko et al, 2005;Stessman et al, 1996) co-morbid illness (Hellström et al, 2004) and depression (Beutel et al, 2017;Chrostek, Grygiel, Anczewska, Wciórka, & Świtaj, 2016;Pinquart & Sorensen, 2001;Sündermann, Onwumere, Kane, Morgan, & Kuipers, 2014;Switaj, Grygiel, Anczewska, & Wciórka, 2014) have been found highly significantly associated with loneliness in older adults in previous studies. The portion of older citizens has been increasing worldwide and Bangladesh is not exception of this.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of hearing and vision problems was operationally defined by the authors (Zhong et al 2018b). Hearing problem was present if the interviewer must speak at a louder volume than usual to help the interviewee hear questions clearly, while vision problem was present if the respondent reported having difficulties in seeing TV or movies.…”
Section: Procedures and Instrumentsmentioning
confidence: 99%
“…Due to the inconvenient transportation in rural regions, Chinese older adults living in these rural areas are more likely to seek treatment from local primary care clinics at their villages. Therefore, primary care has been very wellplaced to provide general healthcare services for Chinese older adults (Li et al 2016;Li et al 2017;Zhong et al 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted among community-dwelling adults in California found the prevalence of moderate-high level of loneliness as 76% (Lee et al, 2018). Another study found the 26.2% of older adults attending primary care in China were suffering from loneliness (Zhong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%